Evolutionary feedbacks for Drosophila aggression revealed through experimental evolution - Anna R. Girardeau; Grace E. Enochs; Julia B. Saltz (Proceedings of the National Academy of Sciences, 2025)
Evolutionary feedbacks occur when evolution in one generation alters the environment experienced by subsequent generations and are an expected result of indirect genetic effects (IGEs). Hypotheses abound for the role of evolutionary feedbacks in climate change, agriculture, community dynamics, population persistence, social interactions, the genetic basis of evolution, and more, but evolutionary feedbacks have rarely been directly measured experimentally, leaving open questions about how feedbacks influence evolution. Using experimental evolution, we manipulated the social environment in which aggression was expressed and selected in fruit fly ( Drosophila melanogaster ) populations to allow or limit feedbacks. We selected for increased male–male aggression while allowing either positive, negative, or no feedbacks, alongside unselected controls. We show that populations undergoing negative feedbacks had the weakest evolutionary changes in aggression, while populations undergoing positive evolutionary feedbacks evolved supernormal aggression. Further, the underlying social dynamics evolved only in the negative feedbacks treatment. Our results demonstrate that IGE-mediated evolutionary feedbacks can alter the rate and pattern of behavioral evolution.